The complete mitochondrial genome of Anthus hodgsoni (Passeriformes: Motacillidae). Issue 1 (1st January 2016) - Sun, Ping; Zhang, Chenling; Pang, Mujia; Qian, Lifu; Pan, Tao; Wang, Hui; Zhang, Baowei
Abstract: Anthus hodgsoni is a species of small passerine bird in the family Motacillidae, which is widely distributed. In this study, we determined the complete mitochondrial genome of A. hodgsoni . The result showed that the total length of the mitochondrial genome was 16, 886 bp and contained 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes and 1 control region. The phylogenetic tree was reconstructed using the Bayesian analysis method and divided into four genera, Anthus, Dendronanthus, Motacilla and Tmetothylacus . The A. hodgsoni which we determined was clustered into genus Anthus and received strong support.